Nyuguh Tradition: Religious and Cultural Harmony in Kampung Adat Kuta, Ciamis, West Java - Fikriya Malihah; Ahmad Habibi Syahid; Reno Wikandaru (Al Qalam, 2022)
Indonesia is a country rich in culture. However, the nation's cultural wealth still has not been studied and is not even recognized by the public. The lack of studies on the cultural richness of this nation is feared that it will cause the nation's own cultural traditions to be unrecognized, until eventually they will disappear and no longer be preserved by the next generation of the nation. This study aims to complete the study of the people of Kuta, especially about the relationship between tradition and religion. The research model used is a literature research model combined with field research. Data collection in this study was carried out in several ways, namely through document searches, direct observation to the Kampung Adat Kuta and conducting interviews with leaders. Based on the research conducted, it was found that the traditional process of Nyuguh carried out by the indigenous people of Kuta is one way for the community to preserve culture, and as an expression of gratitude and efforts to maintain the safety of all residents in the village. The Nyuguh tradition is full of religious values, namely the value of togetherness, simplicity, safety, respect, obedience, balance between religion and culture, and the purification of property. As a part of the culture owned by the people of Kampung Adat Kuta, the Nyuguh tradition is a form of harmonization between the cultural traditions of the ancestral heritage and the Islamic religious beliefs held by the community at this time. The fact that the Nyuguh tradition still survives today with various adjustments in it, shows that harmony between culture and religion can be realized and sustainable among the people of the Kuta Traditional Village.